Literary Conceptualizations of Growth : Metaphors and cognition in adolescent literature - Trites, Roberta Seelinger, 1962- (Children's literature, culture, and cognition ;, 2014)
Literary Conceptualizations of Growth explores those processes through which maturation is represented in adolescent literature by examining how concepts of growth manifest themselves in adolescent literature and by interrogating how the concept of growth structures scholars' ability to think about adolescence. Cognitive literary theory provides the theoretical framework, as do the related fields of cognitive linguistics and experiential philosophy; historical constructions of the concept of growth are also examined within the context of the history of ideas. Cross-cultural literature f.